FARMERS' DECISION TO JOIN THE INDEPENDENT FARMERS COOPERATIVE: KEPUTUSAN PETANI UNTUK BERGABUNG DALAMKOPERASI TANI MANDIRI - Erza Janwar; Ema Hilma Meilani; Ika Sofia Rizqiani (PT. ROCE WISDOM ACEH, 2026)
This study explores the internal and external factors that influence farmers’ decisions regarding cooperative membership. Conducted at the Mandiri Sejahtera Farmers Cooperative in Selaawi Village, Sukabumi, the research employs a quantitative survey method involving all 23 cooperative members. Internal factors include knowledge of cooperatives and economic motivation, while external factors include social support, perceived benefits, and trust in cooperative management. Data were analyzed using multiple linear regression via SPSS. The findings reveal that both internal and external factors significantly affect farmers’ membership decisions, with external factors showing a more dominant influence. An R² value of 0.944 indicates that these factors explain 94.4% of the variation in farmers’ decisions. These results underscore the importance of fostering tangible cooperative benefits and building trust to enhance farmer participation.